Considering gene therapy to protect from X‐linked deafness DFNX2 and associated neurodevelopmental disorders. Issue 4 (27th September 2022) - Defourny, Jean
Abstract: Mutations and deletions in the gene or upstream of the gene encoding the POU3F4 transcription factor cause X‐linked progressive deafness DFNX2 and additional neurodevelopmental disorders in humans. Hearing loss can be purely sensorineural or mixed, that is, with both conductive and sensorineural components. Affected males show anatomical abnormalities of the inner ear, which are jointly defined as incomplete partition type III. Current approaches to improve hearing and speech skills of DFNX2 patients do not seem to be fully effective. Owing to inner ear malformations, cochlear implantation is surgically difficult and may predispose towards severe complications. Even in cases where implantation is safely performed, hearing and speech outcomes remain highly variable among patients. Mouse models for DFNX2 deafness revealed that sensorineural loss could arise from a dysfunction of spiral ligament fibrocytes in the lateral wall of the cochlea, which leads to reduced endocochlear potential. Highly positive endocochlear potential is critical for sensory hair cell mechanotransduction and hearing. In this context, here, we propose to develop a therapeutic approach in male Pou3f4 −/ y mice based on an adeno‐associated viral (AAV) vector‐mediated gene transfer in cochlear spiral ligament fibrocytes. Among a broad range of AAV vectors, AAV7 was found to show a strong tropism for the spiral ligament. Thus, we suggest that an AAV7‐mediated delivery of Pou3f4 complementary DNA in the spiral ligament of Pou3f4 −/ y mice could represent an attractive strategy to prevent fibrocyte degeneration and to restore normal cochlear functions and properties, including a positive endocochlear potential, before hearing loss progresses to profound deafness. Abstract : Hearing loss is the most frequent congenital sensory disability. About 1–3 in 1000 children are affected at birth or during early childhood by severe hearing losswhich is defined as prelingual deafness, with at least half of all cases having a genetic origin. Mutations and deletions in the gene or upstream of the gene encoding the POU3F4 transcription factor cause X‐linked progressive deafness DFNX2 with inner ear malformations and additional neurodevelopmental disorders. Hearing and speech outcomes after cochlear implantation remain highly variable among patients. Pou3f4 −/ y mice show progressive hearing loss, reduced endocochlear potential, and damaged spiral ligament. Among a broad range of AAV vectors, AAV7 shows strong tropism for the spiral ligament. Thus, we suggest that AAV7‐Pou3f4 transduction in newborn Pou3f4 −/ y mice could help to restore cochlear functions and properties, including a positive endocochlear potential, before hearing loss progresses to profound deafness.